2006
DOI: 10.1051/0004-6361:20054112
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances in seven galactic planetary nebulae

Abstract: An observational study of chemical abundances in the galactic planetary nebulae NGC 1535, NGC 2438, NGC 2440, NGC 3132, NGC 3242, NGC 6302, and NGC 7009 based on long-slit spectra of high signal-to-noise ratio in the 3100 to 6900 Å range is presented. We determined the N, O, Ne, S, and Cl abundances from collisionally excited lines and the He and O ++ abundances from recombination lines. ++ /H + derived from recombination and from forbidden lines present smooth variations along the nebular surface of NGC 7009,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…We point out that the wavelength coverage as well as the region covered by the slit/aperture vary in the literature. Krabbe & Copetti (2006) data covering the wavelength range from 3100 Å to 6900 Å, is closer to ours not only in terms of spectral coverage, but also in terms of the elemental abundances and ICFs derived although they use a single slit. Similar to our studie, their study was based on optical spectra alone.…”
Section: Ionic and Total Chemical Abundancessupporting
confidence: 60%
“…We point out that the wavelength coverage as well as the region covered by the slit/aperture vary in the literature. Krabbe & Copetti (2006) data covering the wavelength range from 3100 Å to 6900 Å, is closer to ours not only in terms of spectral coverage, but also in terms of the elemental abundances and ICFs derived although they use a single slit. Similar to our studie, their study was based on optical spectra alone.…”
Section: Ionic and Total Chemical Abundancessupporting
confidence: 60%
“…In PNe, these estimatives show high values. As examples, Liu et al (2006) found t 2 ≈ 0.14 for Hf 2-2, and Krabbe & Copetti (2006) found t 2 ≈ 0.09 for NGC 3242 and NGC 7009 to obtain consistent O ++ /H + estimates derived from RLs and CELs. A discrete estimation of t 2 on the plane of the sky can be computed from point-to-point measurements of temperature, following the procedure proposed by Liu (1998).…”
Section: Magnitude Of the Electron Temperature Fluctuationsmentioning
confidence: 77%
“…Ionic metal abundances were obtained with the ionic routine of the nebular package of the STSDAS/IRAF. The references for atomic parameters used are listed in Table 2 of Krabbe & Copetti (2006). The ionic helium abundances were derived from the strongest lines λ4471, λ5876, and λ6678, using the He i emissivities of Benjamin et al (1999), which are corrected by the effects of collisional excitation.…”
Section: Electron Densities and Temperaturesmentioning
confidence: 99%